Образ послевоенной действительности в повести Виктора Некрасова В родном городе - Bortnowski, Antoni (Studia Rossica Posnaniensia, 2025)
The article delves into the specificity of representing post-war reality in Viktor Nekrasov's novel In the home town. The aim of the analysis is to demonstrate the pivotal role of urban reality portrayal in addressing the story's thematic concerns and reflecting the characters' inner turmoil. Nekrasov's characters grapple with post-traumatic stress disorder, struggling to find their place in a post-war world. The depiction of a hostile and unwelcoming Kyiv mirrors their displacement and inability to reintegrate into civilian life. The analysis examines the portrayal of individual urban elements such as apartment or train station, as well as the city as a whole. Furthermore, it explores how the characters interact with the urban environment and with each other. Ultimately, the article concludes that the portrayal of the post-war city is intricately linked to the novel's ideological underpinnings, suggesting that the end of the war marks only the beginning of a challenging journey toward normalcy for both civilians and soldiers alike. In addition, the article for the first time puts forward the thesis about the novel In the home town as an ideological continuation of In the trenches of Stalingrad, with which it forms a holistic view of the war and its consequences in the works of Viktor Nekrasov.